"Blue is the New Green": Representational Space and the Effective Co-Optation of Environmental Justice Discourses in Pennsylvania's Unconventional Natural Gas Drilling. Issue 3 (November 2014) - Cruger, Katherine M.; Finewood, Michael H.
This paper points to the importance of studying the intersection of public policy debates, spatial practice, and land use by applying Henri Lefebvre's spatial trialectic in a critique of the ongoing debate over hydraulic fracturing in western Pennsylvania. In this case study, the oil and gas industry appropriates established environmental justice discourses to assert that (1) fracking is clean and environmentally responsible, (2) it will help sustain local families and communities for many generations to come, and (3) fracking locally results in scalar, global benefit. Furthermore, the industry employs ad-hominum attacks and debunking strategies to frame anti-fracking activists as impractical alarmists. Through this rhetorical representation of space, the industry defines the process and associated values of fracking as desirable, inevitable, and most importantly, a sustainable process with just outcomes. Ultimately, the material reality of how the risks and benefits are distributed across the local, national, and global landscape through spatial practice is masked. Focusing exclusively on discourse ignores the real material conditions that give rise to and result from that discourse. Therefore, we argue Lefebvre's (1991) trialectic offers a way to address the interplay between representations and discourses of space and material reality.